Field feeding by dabbling ducks around the Ouse Washes, England - Thomas, G J (Wildfowl, 1981)
Around the Ouse Washes wheat Triticum aestivum, barley Hordeum vulgare, and potatoes Solanum tuberosum are the main field crops. Mallard Anas platyrhynchos, Pintail A. acuta, Teal A. crecca and small numbers of Wigeon A. penelope feed on stubble grains in the autumn. In the winter the first two feed on waste potatoes and Wigeon graze on winter wheat leaves. The ducks range freely over fields up to 5 km away, usually two-thirds of the fields being used for only up to a week. The favoured stage of the crop rotation was sprouting winter wheat following an old potato crop. Mallard and Pintail usually flighted to the fields before it was light and returned to the Washes just after daybreak. Another flight occurred in the late afternoon with birds returning at or just after dusk. Wigeon mostly flighted during the day. The largest number of ducks used the fields when there were adverse feeding conditions on the Washes, especially under high flooding and freezing conditions. Allegations of duck damage to crops were largely unfounded in the cases investigated. Yields of winter wheat in fields visited by ducks were comparable to the crop in the remainder of the farm. Trampling was confined to small areas around temporary pools. Dispersal of flocks was affected by shooting over fields on single occasions. Only a small proportion of the available foods were consumed. With more refuges it is almost certain that the carrying capacity of the area would be increased with other species feeding on the fields even if only on a seasonal basis.